"Judging a book by its cover": meditation, memory, and invention in seventeenth-century Ukrainian title pages. Issue 1 (3rd April 2017) - Bartolini, Maria Grazia
ABSTRACT: This article concerns the use of visual paratexts in seventeenth-century Ukraine, and of illustrated title pages in particular. The books under analysis represent three crucial monuments of seventeenth-century Ukrainian sacred oratory. These are: Lazar Baranovych's Truby sloves propovidnykh na narochityia dni prazdnikov (Kyiv, 1674), and Antonii Radyvylovs'kyi's Ohorodok Marii Bohorodytsy (Kyiv, 1676) and his Vinets Khrystov z propovidii nedelnykh (Kyiv, 1688). The author concentrates on the "cognitive" aspect of their titular pages, dealing with them as a rhetorical process that emphasizes meditation, invention, and memory. More specifically, she investigates the correlation between the visual and the written as a specific literary-figurative "mode of thought" that stands in a long Christian tradition of expounding images as meditational tools. She shows how Baranovych and Radyvylovs'kyi interact with this tradition, arguing that their title pages provide readers-viewers with both a machina meditativa, a meditative apparatus for reflecting upon the mystery of the Incarnation, and a machina rhetorica, a repertory of images that the users of the books, often themselves preachers, could use to compose new texts.